Implementation of cisco packet tracer as network simulation in educational environment at SMK Tarbiyatul Banin-Banat Montong School - Amran, Ali; Syaharani, Happy (Institute of Computer Science (IOCS), 2024)
This journal aims to describe the implementation of using Cisco Packet Tracer as a network simulation tool in an educational environment al Tarbiyatul Banin-Banat Montong Vocational High School (SMK) Network simulation is an important method in information technology education, especially in the context of computer network learning This research covers the steps taken in implementing Cisco Packet Tracel at SMK Tarbiyatul Banın-Banat Montong, as well as the benefits that result from using this simulation tool. The research methods include student surveys, as well as classroom observations. The journal is ahead in the use of network simulation technology such as Cisco Packe Tracer in education. As technology continues to evolve, this approach has the potential to continuously improve network leaming and prepare students for the job demands of the digital age. The results showed that the use of Cisco Packet Tracer in network learning at SMK Tarbiyatul Banin-Banat Montong has improved students understanding networking concepts, allowed them to test theories in a safe simulation environment, arid stimulated their interest in pursuing a career in information technology. In addition, the use of this tool also assists teachers in teaching more effectively and efficiently. This article details the practical implementation of Cisco Packet Tracer in an educational environment, illustrates its benefits to students and educators, and provides recommendations for further development in network education at SMK Tarbiyatul Banin-Banat Montong as well as educational institutions in conclusion, the use of Cisco Packet Tracel as a network simulation tool in an educational environment can improve similar the quality of leaming and prepare students for careers in the world of information technology.